1999
DOI: 10.1007/bf03012609
|View full text |Cite
|
Sign up to set email alerts
|

Epidural hematoma following epidural catheter placement in a patient with chronic renal failure

Abstract: Epidural hematoma following epidural catheter placement in a patient with chronic renal failure Purpose: We report a case of epidural hematoma in a surgical patient with chronic renal failure who received an epidural catheter for postoperative analgesia. Symptoms of epidural hematoma occurred about 60 hr after epidural catheter placement. Clinical features: A 58-yr-old woman with a history of chronic renal failure was admitted for elective abdominal cancer surgery. Preoperative laboratory values revealed anem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Thus, CRF is a definite risk factor for spinal haemorrhage, 3 illustrated by two case reports of post‐CNB SHs, where CRF was the only recognized risk factor 114,115 . There are also two cases of CRF with clopidogrel medication, interrupted 1 week before the CNB, and given LMWH peri‐operatively, 82,83 and one additional case with aspirin medication, intraoperative heparinization, and dextran infusion, apart from his renal disease 116 .…”
mentioning
confidence: 99%
“…Thus, CRF is a definite risk factor for spinal haemorrhage, 3 illustrated by two case reports of post‐CNB SHs, where CRF was the only recognized risk factor 114,115 . There are also two cases of CRF with clopidogrel medication, interrupted 1 week before the CNB, and given LMWH peri‐operatively, 82,83 and one additional case with aspirin medication, intraoperative heparinization, and dextran infusion, apart from his renal disease 116 .…”
mentioning
confidence: 99%
“…Although peripheral nerve blocks are used to assist in providing postoperative pain control in ESRD, concern still exists regarding the use of epidural techniques for these patients. [ 15 16 17 ] Hemodialysis has been reported as a risk factor for developing epidural hematoma in hemodialysis patients. [ 15 16 ] However, studies have reported the successful use of epidural analgesia for both obstetrical and nonobstetrical procedures in dialysis patients without developing epidural hematoma.…”
Section: Challenges In Postoperative Pain Management In Chronic Kidnementioning
confidence: 99%
“…[ 15 16 17 ] Hemodialysis has been reported as a risk factor for developing epidural hematoma in hemodialysis patients. [ 15 16 ] However, studies have reported the successful use of epidural analgesia for both obstetrical and nonobstetrical procedures in dialysis patients without developing epidural hematoma. [ 18 19 20 ] Due to the small sample sizes of these reports, it is difficult to provide an estimate of the rate of this complication.…”
Section: Challenges In Postoperative Pain Management In Chronic Kidnementioning
confidence: 99%
“…Traditional surgical complications include wound or catheter site infections (10%), bleeding, wound seroma, failure to provide analgesia, spinal headache, spinal catheter leak (2%), rare epidural hematoma formation [40], rare epidural abscess (Fig. 2), rare meningitis, and rare neurologic injury.…”
Section: Complicationsmentioning
confidence: 99%